Mengembangkan Bahan Ajar Berbasis Local Genius Cirebon sebagai Upaya Membangun Literasi Sains Mahasiswa: Developing Teaching Materials Based on Local Genius Cirebon as an Effort to Build Student Science Literacy - Putri, Dian Permana; Febianti, Yopi Nisa; Muslimin, Sugeng (Pedagogia : Jurnal Pendidikan, 2020)
This study aims to design a Cirebon-based local genius teaching material that is valid, practical and effective in the Basic Natural Sciences course to build student scientific literacy. The research method used is the research and development (R & D) approach. The model development approach used is 4D developed by Thiagarajan. The results of the study showed that teaching materials designed and developed were valid by testing validity twice by three expert validators, consisting of material experts, media experts and practitioners' experts. Teaching materials have been practical based on a limited test on 20 participants who filled out the questionnaire. and in effective tests, teaching materials can improve student scientific literacy, as evidenced by the average n-gain value of 0.417 in the experimental class with the moderate criteria.